Shear bond resistance and enamel surface comparison after the bonding and debonding of ceramic and metallic brackets - José Maurício da Rocha; Marco Abdo Gravina; Marcio José da Silva Campos; Cátia Cardoso Abdo Quintão; Carlos Nelson Elias; Robert Willer Farinazzo Vitral (Dental Press Editora, 2014)
OBJECTIVE: To evaluate, in vitro, the shear bond strength presented by three brands of polycrystalline ceramic brackets and one brand of metallic bracket; verify the adhesive remnant index (ARI) after the tests, and analyze, through scanning electron microscopy (SEM) the enamel surface topography after debonding, detecting the release of mineral particles. METHODS: Sixty bovine lower incisors were used. Three ceramic brackets (Allure(r), InVu(r), and Clarity(r)) and one metallic bracket (Geneus(r)) were bonded with Transbond XT(r). Kruskal-Wallis's test (significance level set at 5%) was applied to the results of share bond and ARI. Mann Whitney's test was performed to compare the pairs of brackets in relation to their ARI. Brown-Forsythe's test (significance level set at 5%) was applied to the results of enamel chemical composition. Comparisons between groups were made with Games-Howell's and the Post-hoc tests. RESULTS: No statistically significant difference was observed in relation to the shear bond strength loads. Clarity(r) brackets were the most affected in relation to the surface topography and to the release of mineral particles of enamel (calcium ions). CONCLUSION: With regard to the ARI, there was a prevalence of score 4 (40.4%). As for enamel surface topography, the Geneus(r) bracket was the only one which did not show superficial tissue loss. The InVu(r) and Clarity(r) ones showed cohesive fractures in 33.3% and the Allure(r) in 50%, the latter being the one that presented most fractures during removal.